AR-AR ISOTOPIC AGE OF LAMPROITE DIKES OF THE CHUA COMPLEX, GORNYI ALTAI - Vrublevskii V.V.; Gertner I.F.; Voitenko N.N.; Polyakov G.V.; Izokh A.E.; Travin A.V.; Krupchatnikov V.I. (My University, 2004)
It is known that artificial impact on oil-and-gas reservoirs frequently induces low-magnitude earthquakes. The problems of induced seismicity are very interesting due to their fundamental importance in the theory of earthquake physics and practical applications. The objective of our paper is to study the seismic activity of saturated porous media induced by fluid injection into a reservoir during oil-and-gas production. Our goal is to formulate a systematic method for the description and interpretation of microearthquake clouds taking into account that microseismicity is induced by changes in pore pressure, which in its turn is controlled by a low-frequency slow Biot wave (a longitudinal wave of the second kind). In order to estimate the changes in pore pressure and stresses in geomaterials, we shall use the classical Biot model, which describes the propagation of elastic waves in an isotropic homogeneous fluid-saturated porous medium. We show that the solution of the corresponding boundary problem and the spatiotemporal distribution of seismic events allow us to estimate the critical value of pore pressure (sufficient for the generation of a microearthquake) and the values of hydromechanical parameters (for example, permeability) of a saturated rock. The suggested method was tested on experimental data.